Peningkatan Layanan Kependudukan dan Catatan Sipil yang Inklusif Melalui Optimalisasi Fasilitas Penyandang Disabilitas di Dinas Kependudukan dan Catatan Sipil Kota Tangerang Selatan - Fauzi, Arief Rachmat; Patadjenu, Syahrifan; Utami, Ratih; Rachmadi Slamet, Dodit (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
The physical, intellectual, mental, and/or sensory limitations experienced should not be an obstacle for persons with disabilities to have the right to live and maintain a decent life. The South Tangerang City Government has proven its alignment with people with disabilities by enacting Regional Regulation Number 18 of 2019 concerning the Implementation of Disability Protection. In its implementation, there are problems in the implementation of facilities, especially facilities and infrastructure for persons with disabilities. This will have an impact on community satisfaction, especially people with disabilities in accessing public services at the Disdukcapil of South Tangerang City. Some findings in the field include that there are still no supporting facilities and infrastructure such as stairs, handrails for wheelchair users, special toilets, misused guide lanes, and no signage for special parking spaces for persons with disabilities. Alternative policies to improve population services and inclusive civil registration include revitalizing facilities and infrastructure, building additional facilities, structuring office areas, and efforts to get closer to people with disabilities in order to fulfill population services. Based on the results of the analysis, it is recommended to carry out an integrated arrangement of the office area. The recommendation was conveyed so that the principles of convenience, security, safety, comfort, health, and independence in going to and utilizing public facilities could be achieved. In addition, the arrangement of the area that is more integrated with other public facilities such as public transportation is expected to facilitate access for the community, especially people with disabilities in accessing services.